HUBUNGAN PENGETAHUAN WANITA PRA-MENOPAUSE DENGAN KESIAPAN DALAM MENGHADAPI MENOPAUSE DI DESA MATANG SAGOE KECAMATAN PEUSANGAN KABUPATEN BIREUEN, TAHUN 2014 - Fitria , Irma (JURNAL KESEHATAN ALMUSLIM, 2016)
Age life expectancy Indonesian women has increased. Currently, age life expectancy Indonesian women is 67 years old. WHO estimates that in 2025 reached 75 years. This means that women have the opportunity to live an average of 25 years since the beginning of the menopause. While in the year 2003-2004 SDKI mention about 21.1% of the population of Indonesia has entered the age of menopause, and approximately 70% of menopausal women experience depressive complaints and other psychological complaints. This confirms that most women are afraid to face the menopause because not prepared to accept reality, and the lack of correct information about the menopause. Mental changes greatly affected the quality of life of a woman undergoing menopause, women’s view of menopause, and knowledge about menopause that will help them understand and prepare themselves through this period better. This research to determine the relationship between knowledge of pre-menopausal women with readiness in the face of menopause, and to know the size of the risk or the relationship. This study used survey methods of analytic cross-sectional approach, conducted in the village of Matang Sagoe Sub Peusangan District Bireuen, which conducted in January 2014. Population consisted of 53 respondents pre-menopausal women. The sampling technique is the total sampling of all populations sampled, the data used secondary data and primary data collected by questionnaires. To test the hypothesis by using Chi-Square test with CI 95% and α = 0.05. From 53 pre-menopausal women is 48 respondents (90.6%) who are ready to face the menopause, with a good knowledge category amounted to 90.6% respondents, and lack of knowledge amounted to 66.7% respondents. And showed there is a relationship between knowledge of pre- menopausal women with menopausal preparedness, with the value of OR = 8.00.